Clinical and Eco-Epidemiological Aspects of a Novel Hyperendemic Area of Paracoccidioidomycosis in the Tocantins-Araguaia Basin (Northern Brazil), Caused by Paracoccidioides sp. - Krakhecke-Teixeira, Alessandra G.; Yamauchi, Danielle H. [UNESP]; Rossi, Alexsandra; de Sousa, Herdson R.; Garces, Hans G. [UNESP]; Júnior, Joaquim L.; Júnior, Antônio O. S.; Felipe, Maria Sueli S.; Bagagli, Eduardo [UNESP]; de Andrade, Heitor F.; Teixeira, Marcus de M. (MDPI, 2022)
Paracoccidioidomycosis (PCM) is the most prevalent systemic mycosis in Brazil. The disease is caused by dimorphic fungi nested within the Paracoccidioides genus. We described 106 PCM cases (47.1 cases/year) at the Tropical Diseases Public Hospital of Tocantins State. PCM was prevalent in males and rural workers over 50 years; the chronic pulmonary form predominated in 67% of cases. The male-to-female ratio was 2.65:1, with more women affected than other endemic regions of Brazil. Urban or indoor activities were reported in women and are ascribed to disease urbanization. qPCR-based assays confirmed the identification of Paracoccidioides DNA in 37 biological specimens. Paracoccidioides sp. DNA was found in 53% of the environmental samples, suggesting autochthonous infections. Therefore, the Tocantins-Araguaia basin must be considered a novel hyperendemic area of PCM in Brazil, reinforcing the importance of including PCM as a notifiable disease, requiring specific diagnosis and health measures.
Keywords: Northern Brazil; paracoccid-ioidomycosis; Paracoccidioides brasiliensis; Paracoccidioides lutzii; Tocantins-Araguaia basin